Trends in organ- and tissue-specific donation refusals in São Paulo, Brazil, a quantitative cross-sectional study - Barbara Rossana Gimenez Hidalgo; Rafael Rodrigo da Silva Pimentel; Marcelo José dos Santos; Edvaldo Leal de Moraes (São Paulo Medical Journal)
ABSTRACT BACKGROUND The mismatch between the supply and demand for organs and tissues for transplantation is one of the reasons for the high rates of donation refusal. A more recent contributing factor has been the COVID-19 pandemic. OBJECTIVES To analyze, through the Terms of Donation of Organs and Tissues, the rates and trends of specific refusals for each organ and tissue from brain-dead donors between 2001 and 2020 in an Organ Procurement Organization. DESIGN AND SETTING This was a cross-sectional, exploratory, and retrospective quantitative study on specific donation refusals conducted in one of the ten Organ Procurement Organizations in São Paulo, Brazil. METHODS The variables collected included year, age, gender, cause of death, type of hospital, and organs and tissues donated and refused. The data were transferred to Stata software for descriptive and inferential analysis, using generalized linear regression to examine time trends. A significance level of P lt; 0.05 was adopted. RESULTS Bones and skin had the highest rates of tissue donation refusal, at 56.40% and 55.37%, respectively. Among solid organs, the pancreas (4.05%) and lungs (5.23%) had the highest refusal rates. In the first decade analyzed, there were increasing time trends in refusals of valves, heart, pancreas, and lungs. In contrast, during the second decade, refusals of valves, kidneys, and pancreas showed decreasing trends. In 2020, the number of refusals for all tissues declined. CONCLUSION To reduce tissue-specific refusals, it is important to address and mitigate family beliefs, myths, and negative attitudes toward organ and tissue donation.